Agency costs and R&D: Evidence from Finnish SMEs - Lotta Väänänen (The Research Institute of the Finnish Economy (ETLA), 2003)
This paper examines empirically how firm ownership structure affects its research- and development (R&D) intensity. To begin with, a principal-agent problem created by the separation of the management of a firm (the agent) and its ownership (the principal) is reviewed, and prior empirical literature is looked at. We acknowledge that the empirical estimation of effects of corporate governance on firm's activities has various problems, and provide evidence that ownership structure is determined endogenously. Using a sample of around 600 Finnish SMEs, the results of the Tobit estimations of firm R&D show that 1) entrepreneur's ownership share has a U-shaped relation with a turning point at 51 percent, 2) employees' ownership share has an inverse U-shaped relation, with a turning point at 47 percent, 3) the presence of a venture capitalist is positively related to R&D intensity. The results from the Tobit regressions cannot be interpreted as conclusive evidence of the actual causality between ownership and R&D, because of the endogeneity of the ownership variables. Instrumental variable estimation is used to attempt to solve the problem. Unfortunately only weak instruments are found and the two-stage least squares method gives no significant results as the standard errors became large. – – Tutkimuksen tavoitteena on empiirisesti analysoida yrityksen omistusrakenteen vaikutuksia sen investointeihin tutkimus- ja kehitystoimintaan (T&K). Aluksi tarkastelemme kysymystä päämies-agentti mallin pohjalta ja käymme läpi empiiristä kirjallisuutta aiheen ympäriltä. Tiedostamme, että kysymyksen ekonometriseen analyysin liittyy ongelmia kuten omistusrakenteen endogeenisuus. Empiirinen analyysi perustuu noin 600:n suomalaisen pkyrityksen kyselyaineistoon. Tobit-estimointien tulokset viittaavat siihen, että 1) yrittäjän omistusosuudella on U:n muotoinen yhteys yrityksen T&K intensiteettiin (alapiste 51%), 2) muiden työntekijöiden omistusosuudella on käänteisen U:n muotoinen yhteys yrityksen T&K intensiteettiin (yläpiste 47%), ja 3) riskisijoittajan omistuksella on positiivinen yhteys T&K intensiteettiin. Nämä estimoinnit eivät tosin anna näyttöä kausaalisuudesta, koska omistusrakenne määräytyy endogeenisesti. Omistusrakenteen instrumentointi ei kuitenkaan tuota merkitseviä tuloksia, koska instrumentit ovat heikkoja.
Keywords: 330; Ownership structure; R&D; agency costs; monitoring; SMEs; Eigentümerstruktur; Forschungs- und Technologiepolitik; Prinzipal-Agent-Theorie; Klein- und Mittelunternehmen; Finnland